Advances in flexible telluride thin-film thermoelectric generators: Deposition, performance, and module fabrication - Theekhasuk, Nattharika; Sakdanuphab, Rachsak; Kianwimol, Supasak; Khumtong, Thanakorn; Toan, Nguyen Van; Sakulkalavek, Aparporn (My University, 2026)
Flexible thermoelectric generators (TEGs) are gaining increasing attention for wearable and skin-attachable electronics due to their ability to harvest low-grade heat from the human body. In this work, p-type Sb2Te3 and n-type Bi2Te3 thin films were deposited by direct current (DC) magnetron sputtering, and the effects of post-deposition annealing on their structural, electrical, and thermal transport properties were systematically evaluated. X-ray diffraction revealed that n-Bi2Te3 exhibited higher crystallinity than p-Sb2Te3, attributed to its lower formation energy. Annealing at 250 °C markedly enhanced the electrical conductivity of both films, with p-Sb2Te3 showing a larger improvement due to concurrent increases in carrier concentration and mobility driven by Te volatilization and the formation of acceptor-type vacancies and antisite defects. In contrast, n-Bi2Te3 exhibited a slight reduction in carrier concentration as a result of compensating donor defects. Consequently, maximum ZT values of approximately 0.5 for p-Sb2Te3 and 0.25 for n-Bi2Te3 were achieved at 513 K. Notably, the compatibility factor (S) values of both films differed by less than a factor of two, indicating favorable thermodynamic pairing for p–n module assembly. A flexible TEG module with 12 thermocouples was subsequently fabricated and delivered an output power of 0.65 μW at ΔT < 25 K, demonstrating promising potential for scalable self-powered wearable electronics.
Keywords: Annealing treatment; Bi2Te3thin films; DC magnetron sputtering; Flexible thermoelectric generator; Low-grade heat harvesting; Sb2Te3